Comprehensive review of the genus Neoperla (Plecoptera: Perlidae) from Guangdong, China: unveiling two new species and a new record - Mo, Raorao; Lin, Aili; Li, Weihai (Zootaxa, 2025)
Fifteen Neoperla species are reviewed from Guangdong Province in southern China. Following a thorough study of material from this province, we have identified and described two new species, Neoperla lianhuashana sp. nov. and Neoperla xiangtoushana sp. nov., which belong to Neoperla (Formosita) subgenus. Additionally, we report the first record of Neoperla hubleyi Stark & Sivec, 2008 from Guangdong, expanding the known geographical range of this species. A distribution map and a provisional key to the known Neoperla species in Guangdong Province are also presented.